Calix[5]phyrin for Fluoride Ion Sensing with Visible and Near Infrared Optical Responses. Issue 16 (30th July 2018) - Higashino, Tomohiro; Kumagai, Atsushi; Imahori, Hiroshi
Abstract: Fluoride (F − ) ion sensing is an important topic due to its roles in health, medical, and environmental sciences. In this regard, colorimetric sensors with a near infrared (NIR) optical response are useful in biological systems because they can avoid interference from endogenous chromophores. Although calix[ n ]phyrins are highly attractive as sensors with the NIR optical response, studies on calix[ n ]phyrins are still limited owing to their intrinsic instability against ambient light and air. In this study, we report the synthesis and characterization of a new calix[5]phyrin bearing one sp 3 ‐hybridized carbon atom as a π‐expanded calix[ n ]phyrin. Upon addition of tetrabutylammonium fluoride, the calix[5]phyrin exhibited distinct NIR absorptions at 908 and 1064 nm as well as a visible color change. Importantly, it revealed an excellent selectivity for F − ion. These results demonstrate that calix[5]phyrins are promising colorimetric and NIR sensors of F − ion. Abstract : That makes some sense ! A calix[5]phyrin bearing one sp 3 ‐hybridized carbon atom as a π‐expanded calix[ n ]phyrin has been synthesized. Upon addition of tetrabutylammonium fluoride, the calix[5]phyrin exhibited distinct NIR absorptions at 908 and 1064 nm as well as a visible color change. Importantly, it revealed an excellent selectivity for F − ion. These results demonstrate that the calix[5]phyrin is a promising colorimetric and NIR sensor of F − ion.